Factors Affecting Audit Delay with Reputation of Public Accounting Firms as Moderation Variables in Food and Beverage Sub Sector Companies in Indonesia stock exchange - Anggraeni, Rr. Dian; Wibowo, Susanto; Herijawati, Etty (Universitas Buddhi Dharma/Fakultas Bisnis/Program Studi Akuntansi, 2020)
This study is to examine the factors that influence audit delay with the moderating variable of public accounting firm reputation in companies listed on the Indonesia Stock Exchange. Data observations were carried out on food and beverage sub-sector companies with financial reports from 2015-2018. The number of sample data is 36 sample data. The data sampling technique used purposive sampling technique. Statistical test using is multiple linear regressions with statistical software STATA. Statistical results show that Audit Tenure has no significant effect on Audit Delay with KAP as a moderating variable with a significance value of 0.724> 0.05, Leverage has no significant effect on Audit Delay with KAP as a moderating variable with a significance value of 0.203> 0.05 and Profitability has a significant effect. on Audit Delay with KAP as a moderating variable with a significance value of 0.015 <0.05.